Public childcare provision and fertility behavior : a comparison of Sweden and Germany - Krapf, Sandra (Budrich UniPress Ltd., 2014)
The author analyzes the relationship between the availability of public childcare for children under age three and the decision to have a first child. One would expect that providing women with the option of returning to work soon after childbirth would reduce the anticipated negative effects of having a child on a woman's career. However, existing research results on this relationship are inconsistent.